Risk Assessment and Risk Indicators in Industrial Institutions in the Gaza Strip: مؤشرات تقييم وإدارة المخاطر في المنشآت الصناعية بقطاع غزة - Mohammed Mohamed Abed Rabbo Almogir (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2018)
The science of risk assessment management is one of the modern science which people around the world is giving a great attention, in order to contribute to the reduction of the destructive effects that followed the industrial revolution and contributed to the spread of risks in all parts of the globe. Hence, the ability to assess the risks, its occurrence, and all aspects affecting the surrounding industrial environment; can contribute to reducing the rates of risk and pollution, and achieve occupational safety and health, as modern science and national and international standards and indicators are calling for industrial protection and safety because of their prominent role in the protection of the whole environment. The problem of the research study is that there are no clear indicators for the assessment and management of risks in the industrial institutions, and there’s a clear lack of procedures that commensurate with the standards imposed by both the Palestinian legislations and environmental standards to reduce environmental risks, which contributes to the integrated system of risk management in industrial institutions This study aimed to highlight the specific criteria and indicators of risk management in industrial institutions, and clarify mechanisms of linking problem solving and risk management in industrial institutions through scientific research, and relying on clear indicators in risk assessment and management. The study had followed analytical descriptive approach of local standards for risk assessment and management, thus risks can be under control, and functional relationship of safety and protection factors and expected risk factors can be analyzed. Researcher had depend on collecting data and analyzing it to answer research question The most important findings of this study are weak reliance on clear indicators in the assessment and management of risks in industrial institutions, and lack of employers ’interest by in relying on risk assessment and analysis methods. The study had recommended the necessity of activating scientific research in the field of risk management in different national sectors due to lack of related studies.